Emotion Regulation Difficulties Are Not Always Associated With Negative Outcomes on Women: The Buffer Effect of HRV - Fantini-Hauwel, Carole; Batselé, Elise; Gois, Cassandra; Noel, Xavier (Frontiers in Psychology, 2020)
The Heart Rate Variability (HRV) is regularly associated with depression and trait emotion regulation. However, the interaction between HRV and emotional disturbances is still debated. Only a few studies indicate that HRV moderates the effect of personality traits involved in psychopathological disorders. Since the regulation of emotions is a transdiagnostic factor for most psychological disorders, the aim of this study was to explore whether HRV moderates the relationship between trait emotion dysregulation and depressive symptoms. We collected data from 142 participants via online questionnaires and HRV measurements at rest. The results confirmed that HRV mitigated the effects of emotion regulation difficulties on depressive symptoms severity. Specifically, when the HRV at rest resulted in greater severity of depressive symptoms in the event of emotional regulation difficulties, high resting HRV remained stable in the same condition. Overall, individuals with a high resting HRV are less affected by difficulties in regulating trait emotions. This suggest that usual emotion regulation tendencies could be overcome by deactivating or inhibitory processes such as those implied in cognitive flexibility reflected through HRV, according to the neurovisceral integration model.